Identifikasi dan prevalensi ektoparasit pada ikan Nila (Oreochromis niloticus) yang dipelihara di keramba jaring apung - Leni Handayani (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2020)
This study aims to determine the types of ectoparasites that attack Tilapia (Oreochromis niloticus) and to determine the level of intensity, prevalence and dominance of ectoparasites. The method used in this study is a survey method with a sampling technique used to inventory the parasites found in Tilapia. The method of data collection was carried out by the field observation method which was carried out in the floating net cages belonging to the community residing in the waters of Lake Sembuluh, Lake Sembuluh I. Observation of ectoparasites was carried out in the external section of the Tilapia, namely the scales, mucus fins and gills. This research was conducted in April - July 2019. The parameters observed in this study included identification of the types of ectoparasites that attacked and the prevalence of ectoparasites in Tilapia and water quality as supporting data. The research data obtained were analyzed descriptively. The results showed that there were 3 types of ectoparasites identified, namely Dactylogirus sp, Tricodina sp and Argulus. The average prevalence of ectoparasites that attacked fish in the cage was Trichodina at 87.67%, Dactylogyrus at 60.00% and Argulus at 43.33%. if the value of water quality, the condition of Lake Sembuluh's water quality is not good, this can be seen from the high value of ammonia, which ranges between 0.02 - 0.10 mg / l and BOD 4.54 - 5.55 ppm. Keywords : Sembuluh, Tilapia, ectoparasites, identification, prevalence